Leviathan, Rebuffing the Notion of Being Identified as a Natural Animal? Festschrift for Willie van Heerden - Dyssel, Allan (Journal for Semitics, 2022)
Leviathan and other sea-monsters in the Hebrew Bible have caused great dissonance amongst biblical scholars. No consensus exists amongst them on how to translate the Hebrew words referring to these mythical monsters. Therefore, a tendency developed amongst exegetes to transfigure these mythical beasts into ordinary animals, to translate them in a vague and general way, or to interpret them as mere symbols. This article investigates ways in which the assumed existence of Leviathan is identified and denied. To gain a better understanding of the nature and function of Leviathan, similar creatures in the ancient Near East are highlighted with a focus on sea-monsters and dragons associated with the primeval sea. These findings propose not only a more distinct epitome of Leviathan, but also of other monsters associated with the primeval waters (Rahab, tanninim, behemoth, and dag gadol), as depicted in the Old Testament. These beasts, interpreted against the magico-mythical cosmology of the ancient Near East and the Old Testament, should be seen as mythical creatures assumed to be real by the ancient audience of the biblical text. In striving for fidelity and loyalty to both the text and the current reader, translations should reflect the foreignness of Leviathan and other monsters or dragons to the contemporary reader.